Implementación de una máquina electromecánica automatizada para el sembrío de semillas para la empresa agrónoma Patricia Pinto, ubicada en la parroquia de Izamba del cantón Ambato de la provincia de Tungurahua. - Alanuca Yanchaguano, Byron Paul (2021)
. This paper describes the techniques and elements used in the implementation of an automated electromechanical machine for sowing seeds in the agricultural company "Patricia Pinto" located in Izamba parish, Ambato canton Tungurahua province, prototype that will optimize the planting process, which involves factors such as saving labor, time and cost of production. The implementation of the prototype has stages such as the selection of elements from the requirements of the company, the design and construction of the mechanical elements such as the dispenser, responsible for the correct passage of the number of seeds at certain times, this through a gate type mechanism driven by a servomotor, another stage that stands out in the prototype is the construction of the harrow type mechanism, Another outstanding stage in the prototype is the construction of the harrow type mechanism, since it is in charge of receiving the seeds from the output of the metering unit, opening the furrow, depositing the seed and covering the soil, actions that are directly related to the speed of 11m/min that the motor reducer provides for the displacement of the prototype, which has a display device located in the upper front part, which allows the monitoring of the land to be sown. With the implementation of the semi-automatic seeding prototype in the seeding process, a reduction of 53% in time and 33% in raw material was achieved, resulting in a 66% reduction of the production cost compared to the manual seeding method.